Analysis of Marketing Mix and Creativity towards MSME Business Development in Medan City - Dian Sari; Irawan (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
The study aims to explore the influence of Marketing Mix and Creativity on MSME Business Development in Medan Perjuangan". The research method used is a quantitative model, using a questionnaire as a data collection tool distributed to 75 respondents. Data analysis in this study used multiple linear regression analysis with partial (ui t) and simultaneous (F test) testing. The results showed that simultaneously the marketing mix and creativity variables had a positive and significant effect on business development. The results of the study partially marketing mix and creativity have a positive and significant effect on business development. The contribution of the influence of marketing mix and creativity on business development is relatively high at 84.1%. The implications of the results of this study are able to prove that the marketing mix and creativity are very important to be able to increase the business development of MSMEs in Medan city.